2018
DOI: 10.1002/pon.4612
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of adherence to exercise interventions during and after cancer treatment: A systematic review

Abstract: ObjectiveExercise interventions benefit cancer patients. However, only low numbers of patients adhere to these interventions. This review aimed to identify predictors of exercise intervention adherence in patients with cancer, during and after multimodality cancer treatment.MethodsA literature search was performed using electronic databases (PubMed, Embase, and Cochrane) to identify relevant papers published before February 1, 2017. Papers reporting randomized controlled trials, conducted in adult cancer patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
165
1
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(183 citation statements)
references
References 77 publications
(398 reference statements)
14
165
1
3
Order By: Relevance
“…For example, a barrier to PA not included in the PABAC measure may be lack of knowledge regarding types of PA that are safe to do. Another limitation is that this study did not assess survivors’ PA prior to their cancer diagnosis, which has been shown to be a determinant of exercise behavior post-cancer diagnosis [40]. Additionally, although the developed PABAC measure and its 4 unique subscales (symptoms, cognitive, logistical and clinical) exhibited adequate psychometric properties in our sample, future research is needed to further validate this scale in other cancer populations.…”
Section: Discussionmentioning
confidence: 98%
“…For example, a barrier to PA not included in the PABAC measure may be lack of knowledge regarding types of PA that are safe to do. Another limitation is that this study did not assess survivors’ PA prior to their cancer diagnosis, which has been shown to be a determinant of exercise behavior post-cancer diagnosis [40]. Additionally, although the developed PABAC measure and its 4 unique subscales (symptoms, cognitive, logistical and clinical) exhibited adequate psychometric properties in our sample, future research is needed to further validate this scale in other cancer populations.…”
Section: Discussionmentioning
confidence: 98%
“…Community‐based programs are generally perceived to be more accessible and affordable and reduce the barriers of distance, cost, and time compared with participation in HCP‐supervised exercise programs . In several community settings, fitness instructors are trained specifically in cancer, including exercise guidelines and prescription, to supervise the exercise sessions/classes.…”
Section: Types Of Programmingmentioning
confidence: 99%
“…There is evidence to suggest that the sampling approach taken by Clifford et al may also be limiting, as barriers to (or correlates of) PA differ between patient populations of differing cancer types . For example, an integrated data analysis involving 23 841 cancer patients reported differences in predictors of PA behaviour between cancer types .…”
Section: Introductionmentioning
confidence: 99%